2003
DOI: 10.1056/nejmoa021835
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Microalbuminuria in Type 1 Diabetes

Abstract: Frequent regression of microalbuminuria in patients with type 1 diabetes indicates that elevated urinary albumin excretion does not imply inexorably progressive nephropathy. Identification of the multiple determinants of the regression of microalbuminuria has implications for current theories about the mechanisms of early diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
489
8
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(561 citation statements)
references
References 44 publications
(32 reference statements)
45
489
8
10
Order By: Relevance
“…In a recent 6-year follow-up analysis of Type 1 diabetic patients with AER levels between 30 and 299 µg/min at base-line, regression of microalbuminuria was defined both as an absolute AER value of less than 30 µg/min, and as a 50% reduction of AER. This was done to make the estimate independent of the AER lower threshold [24]. Both assessments gave a similar cumulative proportion of patients reverting to normoalbuminuria (59% and 58% respectively, for the 6-year interval), which is similar to the proportion found in this study (50.6% in 7 years).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a recent 6-year follow-up analysis of Type 1 diabetic patients with AER levels between 30 and 299 µg/min at base-line, regression of microalbuminuria was defined both as an absolute AER value of less than 30 µg/min, and as a 50% reduction of AER. This was done to make the estimate independent of the AER lower threshold [24]. Both assessments gave a similar cumulative proportion of patients reverting to normoalbuminuria (59% and 58% respectively, for the 6-year interval), which is similar to the proportion found in this study (50.6% in 7 years).…”
Section: Discussionsupporting
confidence: 73%
“…Secondly, a valid AER estimation was obtained in 63.5% of potentially available patients (352/554). Although prospective studies carried out in single centres have a higher follow-up rate [22,23], the proportion of patients completing the follow-up tends to decrease with time when large groups of patients are recruited [24], and this is particularly true given the broad European scope of the EURODIAB multicentre study. Patients not available at follow-up had worse metabolic control, as indicated by higher HbA 1 c and triglyceride concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between reduction of urinary albumin and dyslipidemia were reported in a cohort study of 386 patients with type 1 diabetes [26]. In this study, along with low levels of glycosylated hemoglobin and low systolic blood pressure, low levels of both cholesterol and triglycerides were independently associated with regression of microalbuminuria.…”
Section: Relationships Between Dyslipidemia and Progression Or Regressupporting
confidence: 60%
“…Regression of the earlier stages of microalbuminuria has been demonstrated following antihypertensive treatment, and one prospective observational study reported that, over a 7.5-year follow-up period, regression occurred in 35% of 79 type 1 patients with microalbuminuria (in 39% of patients treated with an ACE inhibitor and in 13% of untreated patients). In another study, a reduction (>50%) in the urinary AER was observed in 58% of 386 microalbuminuric type 1 diabetic patients, but this reduction was transient in many patients, the follow-up period was shorter and the drop-out rate was 47% [30].…”
Section: The Changing Course Of Diabetic Kidney Diseasementioning
confidence: 92%